Hydrogen production through gasification and dark fermentation (2016)
New efforts in the search of alternative clean and renewable energy to replace the current energy precursors have been assessed in order to reduce emissions to the environment. Lignocellulosic Biomass (LB) can be used to produce bioenergy due to its high energy potential and availability. The main objective of this thesis is to evaluate the production of hydrogen through air gasification and dark fermentation using lignocellulosic biomass as feedstock. For this purpose, the methodology was divided in two sections: experimental and simulation procedures. The experimental procedure involves the production of a hydrogen-rich synthesis gas through gasification and the use of the commercial strain T. Thermosaccharolyticum ATCC 7956 to produce hydrogen though dark fermentation. Two different gasification configurations were tested: first, using only lignocellulosic biomass as feedstock and then, mixtures between the raw material and an adsorbent (in this case, quicklime) were fed in the gasifier. For the dark fermentation procedure, a previous pretreatment stage of the raw material was included. Subsequently, pure sugars and hydrolysates (from the pretreatment stage) were tested as carbon source for the hydrogen production using the commercial strain. In the simulation approach, six (6) scenarios for hydrogen production were assessed from the techno-economic, energetic and environmental point of view, considering the biorefinery and stand-alone pathways. As a consequence, the use of low cost and high available adsorbents in the gasification procedure increased the hydrogen selectivity. Hydrogen content was not detected in the dark fermentation procedures; however, high concentration of other metabolites was evidenced, which presents a future scenario for the implementation of alternative process schemes using this microorganism. The results of the simulation procedure demonstrated that the production of hydrogen based on the concept of a biorefinery can improve the profitability, energy efficiency and reduce the emissions of the processes compared to the stand-alone way (Texto tomado de la fuente)